BPJS Ketenagakerjaan as a Fiscal Instrument in Ensuring the Stability of Workers' Welfare in Indonesia - Tedi Hermansyah; Muflihul Fadhil; Muhammad Habibi Siregar; Muhammad Irwan Padli Nasution; Yusrizal; Muhammad Ridwan (Yayasan Darussalam Bengkulu, 2026)
Background: The global economy in 2026 faces increasingly complex challenges, ranging from trade fragmentation to geopolitical tensions that trigger commodity price volatility. In facing these dynamics, the Indonesian Government, through the 2026 Macroeconomic Framework and Main Fiscal Policy Principles (KEM-PPKF), positions the State Budget (APBN) as the main shock absorber to maintain macroeconomic stability. This research aims to elaborate on the strategic role of BPJS Ketenagakerjaan as a fiscal instrument in ensuring the stability of workers' welfare in Indonesia. Method: Using a qualitative approach and literature review, this analysis explores how social security can function as an automatic stabilizer that supports national economic resilience Results: The findings show that BPJS Ketenagakerjaan has evolved into a major pillar of social protection. However, significant structural challenges remain in reaching informal sector workers and achieving closer policy synchronization between the social security system and the national fiscal agenda. Conclusion: The study concludes that the integration of social security into the national fiscal strategy is urgently needed to transform the paradigm of social protection from a cost burden into a strategic investment that supports inclusive and sustainable economic resilience.